UJI BANDING LIMBAH CAIR IKAN, AZOLLA DAN LIMBAH KULIT PISANG SEBAGAI NUTRISI TAMBAHAN UNTUK KUALITAS PRODUKSI TANAMAN CABAI RAWIT (Capsicum frutencens L.) - N. F. Rochmana; Ngadiani Ngadiani (FMIPA : Universitas PGRI Adi Buana, 2017)
Household waste in the form of fish waste, azolla pinnata, and banana peel waste is a waste that has not been utilized optimally. The potential waste can be utilized as a raw material of organic nutrients with macro elements more complete than an-organic nutrients. Giving various variations of organic liquid nutrients can be used to chili (Capsicum frutencens L.). This study aims to determine the effect of different variations of organic liquid nutrient on the quality of chili production (Capsicum frutencens L.). The type of this research is quantitative research with experimental method using Completely Randomized Design consisting of 3 treatments 6 replications, so that there are 18 experimental units adn placed randomly was fish waste 20% (N1), 20% Azolla Pinnata (N2), and banana peel waste 20% (N3). Observations were made on three parameters of production quality is colour, taste, and wet weight. Technical of data analysis using One-way ANOVA with significance level of 0,05. One-way ANOVA test results on the quality of chili production is P>0,05. One-way ANOVA test results showed no signification on the quality of chili production (Capsicum frutencens L.). Keywords: Organic Liquid Nutrition, Liquid Waste Fish, Azolla Pinnata, Banana Peel Waste, Quality Productions of Plants, Chili.